Recurrent myelitis. Issue 3 (March 1996) - Pandit, L; Rao, S
Abstract : Three patients presented with acute complete transverse myelopathy which relapsed several times at the same site. These patients, two women and one man, had two to five attacks spanning three to seven years. All patients underwent detailed investigations including a complete myelogram and serial evoked potential studies. Oligoclonal bands were present in the CSF in one patient. Brain MRI was normal in two patients; MRI of the spinal cord was abnormal and showed cord oedema with multiple areas of hyperintense signals on T2 and proton density weighted scans and hypointense signals on T1 weighted images in areas corresponding to the clinical level, suggesting an inflammatory/demyelinating disorder. These patients may represent a relapsing demyelinating disorder restricted to the spinal cord, distinct from multiple sclerosis.